PERKEMBANGAN KEMATANGAN GONAD DAN TIPE PEMIJAHAN IKAN SELAIS (Ompok hypophthalmus) DI RAWA BANJIRAN SUNGAI KAMPAR KIRI, RIAU [Development of gonad maturity and spawning pattern of Ompok hypophthalmus in floodplain of Kampar Kiri River, Riau] - Djadja Subardja Sjafei; Charles P.H. Simanjuntak; M. F. Rahardjo (Jurnal Iktiologi Indonesia, 2008)
The main objective of the study was to determine gonad maturity development and spawning pattern of O. hypophthalmus in floodplain of Kampar Kiri River. Samples were collected from June to December 2006 on a monthly basis. Biological samples were collected from a total of 474 O. hypophthalmus of which 249. females and 224 males were confirmed by macroscopic and histological analysis. Five gonad maturity stages were described based on the macroscopic and histological analysis. The dynamics of oocyte development of O. hypophthalmus, indicated a synchronism of maturation. Oocyte diameter distribution suggested that this species could be grouped as total spawner and iteroparous species.